2019
DOI: 10.1038/s12276-019-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

Arginase II activity regulates cytosolic Ca2+ level in a p32-dependent manner that contributes to Ca2+-dependent vasoconstriction in native low-density lipoprotein-stimulated vascular smooth muscle cells

Abstract: Although arginase II (ArgII) is abundant in mitochondria, Ca 2+ -accumulating organelles, the relationship between ArgII activity and Ca 2+ translocation into mitochondria and the regulation of cytosolic Ca 2+ signaling are completely unknown. We investigated the effects of ArgII activity on mitochondrial Ca 2+ uptake through mitochondrial p32 protein (p32m) and on CaMKII-dependent vascular smooth muscle cell (VSMC) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…In addition to experimental evidence from transgenic mice that Bcl6 and Stat3 regulate M1 genes, we found that 21 of the genes in module AD1 are Stat3 upstream regulators, eight of which were recently shown in transgenic mouse studies to be involved in AD pathology ( MAPK1 62 , RHEB 63 , SUMO1 64 , VPS35 12 , GSK3B 65 , DYRK1A 66 , EPHA4 67 ) or in Parkinson’s disease ( PAK4) 68 . Recently, Stat3 inhibition was shown to inhibit human astrocyte differentiation and promote neural progenitor-cell differentiation 69 and also to ameliorate astrogliosis in AD model mice 70 .…”
Section: Discussionmentioning
confidence: 71%
“…In addition to experimental evidence from transgenic mice that Bcl6 and Stat3 regulate M1 genes, we found that 21 of the genes in module AD1 are Stat3 upstream regulators, eight of which were recently shown in transgenic mouse studies to be involved in AD pathology ( MAPK1 62 , RHEB 63 , SUMO1 64 , VPS35 12 , GSK3B 65 , DYRK1A 66 , EPHA4 67 ) or in Parkinson’s disease ( PAK4) 68 . Recently, Stat3 inhibition was shown to inhibit human astrocyte differentiation and promote neural progenitor-cell differentiation 69 and also to ameliorate astrogliosis in AD model mice 70 .…”
Section: Discussionmentioning
confidence: 71%
“… 6 Moreover, we have reported that ArgII protein and its activity participate in the Ca 2+ flux between mitochondria and the cytosol in a p32-dependent manner. 13 , 48 Here, we propose two novel functions for ArgII: First, that ArgII regulates CaMKII-dependent Parkin activation and its translocation to mitochondria ( Figure 4 ); and second, that ArgII protein negatively regulates Parkin-dependent p32 ubiquitination ( Figure 8 ). However, we did not determine the mechanism by which ArgII downregulation increased [Ca 2+ ]c, although p32 knockdown did increase [Ca 2+ ]c. We conclude that Ca 2+ moved into the cytosol from elsewhere, as p32 facilitated Ca 2+ movement from the cytosol to mitochondria.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies indicated that the activation of the GPR40 enhanced PAK4 S474 phosphorylation [ 23 ]. CAMP-response element-binding (CREB) becomes activated by PAK4 phosphorylation, which in turn induces gene expression of KDM6B, which mediates inflammatory gene expression and regulates microglia polarization [ 24 , 25 ]. In our present study, we demonstrated that the GPR40 activation by GW9508 significantly upregulated the expression of p-PAK4, p-CREB, KDM6B, CD206, and IL-10, but downregulated the protein levels of IL-1β and TNF-α in the neonatal CNS at 24 h post-GMH.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of GPR40 potentiated the phosphorylation of p21-activated kinases4 (PAK4) in mouse islet cells [ 23 ]. Moreover, phosphorylated PAK4 has been shown to mediate the phosphorylation of CAMP-response element-binding (CREB), which promoted the protection of dopaminergic neurons in a rat model of PD and preserved motor function [ 24 ]. Recent studies also revealed that CREB induces the gene expression of histone H3 lysine 27 (H3K27) demethylase (KDM6B), which plays a role in the regulation of inflammatory gene expression and regulates phenotype switching of microglia from the M1 to M2 state [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%